Effect of grain content on the nutritive value of whole-plant corn silage - Sonon, R.N. Jr.; Dalke, B.S.; Holthaus, D.L.; Pfaff, L.; Bolsen, K.K.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This experiment was conducted to determine the effect of grain content on the nutritive value of corn silage. Whole-plant silage dry matter (DM) increased, whereas neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents decreased as the level of grain increased from 0 to 65% in the reconstituted, whole-plant, corn silages. Using sheep as a model, voluntary DM intake and DM and organic matter (OM) digestibility increased, but crude protein (CP) and ADF digestibilities decreased linearly as grain content increased from 0 to 52.5%. Our results indicate that the optimum level of grain in whole-plant corn silage to maximize the nutritive value of a high silage-based ration was about 52.5%.
Keywords: Beef; Corn; Silage; Grain content; Nutritive value